Hubungan Work-Life Balance dengan Produktivitas Mahasiswa Entrepreneur - Abim Khaffi Maulana; Jos Bram Tamba; M. Irfandi Syahputra; Muhammad reyhan Satria; Saidun Hutasuhut (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to determine the relationship between work-life balance and the productivity of student entrepreneurs who play dual roles as students and entrepreneurs. The research method used a quantitative approach with a correlational survey design. The study sample consisted of 110 student entrepreneurs selected through a purposive sampling technique. The research instrument was tested for validity and reliability, with all items declared valid and having a Cronbach's Alpha value of 0.930, indicating excellent internal consistency. The results of the normality test showed that the data were normally distributed, allowing for a Pearson correlation analysis. The main findings of this study show that work-life balance has a very strong and significant relationship with the productivity of student entrepreneurs, indicated by a correlation value of 1.000 with a significance level of 0.000. This indicates that the better students manage the balance between study, business, and personal life, the higher their business productivity will be. This study confirms that work-life balance is a crucial factor in supporting students' success in optimally carrying out dual roles. These findings are expected to serve as a basis for students, educational institutions, and other relevant parties in designing strategies to increase the productivity of student entrepreneurs.